HUBUNGAN PENDIDIKAN, BUDAYA, TEMAN SEBAYA DENGAN PERNIKAHAN USIA MUDA DI KECAMATAN KANDANGHAUR INDRAMAYU TAHUN 2018 - Prameshya Sekar Galuh Pratitis Widiatmoko; Sri Winarni; R. Djoko Nugroho; Atik Mawarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The marriage limit according to the BKKBN through the GenRe (Generation of Planning) program is 21 years for women and 25 years for men. Based on data from the Ministry of Religion, the highest age of young marriages in the district is in Kandanghaur District with 246 samples from 66 PUS (Simple Random Sampling) women with a case control study approach. This study aims to analyze several factors related to the marriage of PUS Muda women in Ilir Village and Parean Girang Village, Kandanghaur District, Indramayu Regency. The results obtained that there is a relationship between education (p = 0.025; OR = 3,619) and friends (p = 0.014; OR = 4.0252) with young marriage. There is no relationship between culture (p = 1,000; OR = 1,000) and young marriage. The highest percentage is peers supporting young marriages (69.7%).